Southeast Asian Sovereign Wealth Funds: Tracking the Internationalization Path of Companies Piloting an Emerging Region - Tan, Jonathan Thiam Lye (2013)
Southeast Asia has its groove back, becoming the economic force that had been anticipated in the early 1990s. The growth came from the rise of consumer class, global demand for resources, low-cost production, favorable public policy and bold ambitions. However to date, there is little understanding on the motive of internationalization by Southeast Asian sovereign wealth fund‟s (SWFs) subsidiaries. These government-linked companies (GLCs) are growing quickly and expanding overseas rapidly. Their growth has unique characteristics related to their export-oriented and supportive government policies. Using qualitative case studies developed from Singaporean and Malaysian SWFs, the paper probe the ownership advantages, strategic drivers and governance structure of these companies. The analysis of these cases led to the development of six testable propositions focused on the motives of these subsidiaries, whose direct investments dominate North, South and Southeast Asia. This research aims to lay a foundation in international investments for future research on Southeast Asian sovereign wealth funds.